(untitled) (Bangladesh Journal of Medical Science, 2024)
Background Respiratory distress in neonatal period is of diverse etiology and require timely diagnosis and treatment for a good outcome. This study was aimed to determine the outcome of neonates having respiratory distress admitted in the NICU of a tertiary care hospital. Methods This prospective study was conducted in the neonatal intensive care unit of Dr. M R Khan Shishu Hospital & ICH, from July 2021 to June 2022. Neonates presented with signs of respiratory distress were enrolled in the study. History, examination and investigations were performed to find out various etiologies. Neonates were managed accordingly and were followed up to hospital stay. Primary outcome was measured in terms of discharge and death, and secondary outcomes were pattern of respiratory supports required. Data was analyzed using SPSS 20. Results Among 1225 admitted newborns, 720 (59%) had respiratory distress. Mean gestational age was 37.54 ± 2.1 weeks and mean birth weight was 2692.96 ± 651 g. Common causes of respiratory distress were sepsis (35.4%) and perinatal asphyxia (27%) followed by transient tachypnea of newborn (11.4%). Most of the babies required only nasal oxygen support (72%) and 15% were treated with CPAP and 8% got mechanical ventilator. Mortality rate was 2.5% and congenital pneumonia was significantly associated with neonatal death (p=0.02). Conclusion The common causes for respiratory distress were sepsis, asphyxia, TTNB, RDS, MAS and congenital pneumonia. Congenital pneumonia was significantly associated with mortality. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 812-817